Threatened, protected, and rare species of vascular plants in spring complexes in the central part of Polish Pomerania - Osadowski, Zbigniew (Biodiversity: Research and Conservation, 2006)
Within 46 individually researched spring complexes in the central part of Polish Pomerania, the presence of 101 protected, threatened, and rare species was noted. Of these species, 75 were directly linked with underground water outflow. The number of species involved in various habitats ranged from 8 to 33, as 8 were recorded in spring communities, 10 in rush and sedge communities, 33 in mesotrophic rich fens, 28 in meadows and tall forb communities, 12 in alder woods, 18 in alderash woods, and 28 in beech woods and oak-hornbeam woods. The flora of the studied spring ecosystems includes 49 protected species, 41 of which are strictly and 8 partly protected in Poland. Particular care and attention should be directed to the 65 species that are endangered or vulnerable. Among them, 3 are endangered on the European scale: Cypripedium calceolus, Hammarbya paludosa and Saxifraga hirculus.